Linguistics and complexity: Phonetics as an interdisciplinary science - Nocetti, Francisco Antonio (Interpretextos revista semestral de creación y divulgación de las humanidades (Colima), 2024)
This article explores the interdisciplinary relationship between phonetics and acoustics, addressing this connection from the perspective of complex thinking. It provides a historical introduction and fundamental concepts of phonetics, linguistics, and complexity, tailored for a non-specialized audience. Despite these disciplines initially appearing distant and independent, their connection dates back to the early days of their existence as sciences. Their evolution is briefly analyzed, and the need for a deeper transdisciplinary integration is highlighted to optimize their potential in studying human language and its practical applications.